Planning Regimes in Accra, Ghana. - Frimpong, Jesse (University of Waterloo, 2017)
ABSTRACT The purpose of this research is to identify why different planning regimes exist in Accra, Ghana. While addressing this question, many other issues are addressed such as: 1. What is the process of planning in various communities in Accra? 2. What is the cause of the absence of planning in many low-income settlements? 3. How has colonisation shaped current planning processes in Accra? A qualitative approach grounded in a literature review and key informant interviews reveal why different planning regimes exist. The study shows that three distinct planning regimes exist in the city of Accra, because of the complexities associated with planning. The multiple players and actors involved in planning, such as international funders, local and international NGOs, customary landowners, and individuals all impact planning which causes different residential planning regimes across Accra. The lack of adequate funding, indigenous communities, class structures, overstepping of planning laws, are all among the many factors affecting neighbourhoods in Accra. Recommendations focused on good planning practices and better implementation laws. Most importantly, the central theme and overall advice focused on developing planning practices in Accra, that fit the unique nature of the African landscape, values, and culture.
Keywords: Accra; Ghana; africa; planning; planning regimes